Method for preparing copper-based catalyst by using solution plasma and application of copper-based catalyst
The preparation of copper-based catalysts through solution plasma technology solves the problems of low activity and poor stability of existing hydrogenation catalysts, and realizes an efficient process of converting carbon dioxide into methanol, which improves the stability and activity of the catalyst.
Patent Information
- Application Number
- CN202411263723.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-31
AI Technical Summary
Existing hydrogenation catalysts have low activity, poor selectivity, poor stability, low carbon dioxide conversion rate, high reaction energy consumption, and difficult to efficiently convert carbon dioxide into useful chemicals.
The copper-based catalyst is prepared by solution plasma technology. Through the mixing of acyclic alcohol, copper salt and support and high-pressure pulse current treatment, the pH value and mechanical mixing are adjusted to prepare a copper-based catalyst with high active sites and good dispersion. And used in carbon dioxide hydrogenation reaction.
The conversion rate of carbon dioxide and methanol yield are improved, the stability and activity of the catalyst are enhanced, the energy consumption of the reaction is reduced, and the efficient carbon dioxide conversion process is achieved.
Smart Images

Figure CN119215891A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalysts, and in particular relates to a method for preparing a copper-based catalyst by utilizing solution plasma and application thereof. Background Art
[0002] Carbon dioxide is the main greenhouse gas. Its excessive emission leads to the intensification of the atmospheric greenhouse effect and accelerates global warming. Under the background of increasingly severe global climate change, reducing carbon dioxide emissions has become one of the hot topics of global research. At the same time, carbon dioxide is a non-toxic and sustainable resource. Among various resource utilization methods, "atmospheric carbon capture and utilization" is widely recognized. In terms of the catalytic conversion and utilization of carbon dioxide, catalysts play a vital role in this process.
[0003] The art generally utilizes catalysts to convert carbon dioxide captured from the atmosphere into useful chemicals, such as methane, methanol, etc. Through hydrogenation catalytic reaction, carbon dioxide can be converted into a series of platform chemicals (hydrocarbon compounds), which have high energy density and wide application prospects. In order to efficiently convert and utilize carbon dioxide, the art has been exploring catalysts, and high-performance catalysts can improve the conversion rate of carbon dioxide and the selectivity of target products, reduce energy consumption under reaction conditions, thereby achieving efficient carbon dioxide conversion process. However, the hydrogenation catalysts prepared by the prior art have low activity, poor selectivity, and poor stability, and it is urgent to develop new hydrogenation catalysts.
[0004] Those skilled in the art improve the structure and performance of catalysts through various methods. As a new method applied in the field of materials, the solution plasma preparation method has gradually shown its advantages in material size regulation in this field. This method can achieve precise control of nanoparticle size, morphology and structure by adjusting reaction conditions (such as solution concentration, temperature, pH value, etc.), so it has strong scalability.
[0005] Therefore, the present invention prepares a new type of hydrogenation catalyst based on the solution plasma preparation method and expands its application method. Summary of the invention
[0006] Based on the above content, in order to solve the problems of low carbon dioxide conversion rate, large number of chemical reagents required for hydrogenation catalysts and low activity, poor selectivity of target products, and high reaction energy consumption, the present invention proposes a method for preparing a copper-based catalyst using solution plasma and its application in carbon dioxide hydrogenation.
[0007] A method for preparing a copper-based catalyst using solution plasma,
[0008] The method comprises:
[0009] 1) Take acyclic alcohol and dispersant and mix them evenly to obtain a mixed solution, add copper salt and mix evenly, adjust the pH value of the solution, and transfer the solution to Figure 1 The solution is treated with plasma in the device shown to obtain a plasma solution;
[0010] 2) taking out the plasma solution, adding the carrier powder to perform mechanical mixing, centrifuging and drying the solution to obtain the copper-based catalyst powder.
[0011] As a preference,
[0012] Step 1) the acyclic alcohol is isopropanol;
[0013] Step 1) the dispersant is water, and the acyclic alcohol and the dispersant are prepared in a volume ratio of 1: (9-10);
[0014] Step 1) The copper salt is copper nitrate trihydrate, and its dosage is 0.795-0.938 g / L mixed solution.
[0015] As a preference,
[0016] Step 1) The process of adjusting the pH value of the solution is: adding citric acid aqueous solution to adjust the pH value of the solution to 2.9-3;
[0017] The concentration of the citric acid aqueous solution is 0.1-0.2 mol / L.
[0018] As a preference,
[0019] Step 1) The solution plasma treatment is to start the high-voltage pulse current while stirring, keep discharging for 15 minutes, then pause the discharge for 5 minutes, continue the discharge for 15 minutes, and end the discharge after the cycle discharge for 45 minutes. The equipment parameters are as follows:
[0020] The voltage is 5-6 kV, the frequency is 20-30 kHz, and the pulse width is 2-3 μs.
[0021] As a preference,
[0022] Step 2) The carrier powder is zeolite molecular sieve and / or hydrotalcite and / or alumina and / or cerium oxide and / or zinc zirconium oxide, and the amount thereof is 5-6.5 g / g copper salt.
[0023] As a preference,
[0024] Step 2) The mechanical mixing is carried out at room temperature and stirred for 12 to 15 hours.
[0025] Application of a copper-based catalyst,
[0026] The copper-based catalyst is used for titanium dioxide hydrogenation reaction.
[0027] As a preference,
[0028] When the application is:
[0029] The copper-based catalyst powder is tableted and sieved to obtain catalyst particles, silicate minerals are added and mixed evenly, the mixture is transferred to a carbon dioxide hydrogenation reactor, and the mixed gas is introduced into the carbon dioxide hydrogenation reactor to carry out a hydrogenation reaction.
[0030] As a preference,
[0031] The tabletting and screening is to pass the formed catalyst particles through a 40-60 mesh sieve;
[0032] The silicate mineral is quartz sand, and its usage is 5-5.2 g / g catalyst particles;
[0033] The quartz sand is pickled with hydrochloric acid at a concentration of 16-18 wt%.
[0034] As a preference,
[0035] Step 4) the mixed gas includes carbon dioxide, hydrogen and nitrogen, and the carbon dioxide, hydrogen and nitrogen are inflated according to a volume ratio of 1: (2.5-3.5): (0.5-1.5) by a mass flow meter, and the total gas flow rate is controlled at 50-55 mL / min;
[0036] Step 4) The hydrogenation reaction is carried out at 300-350°C with a controlled pressure of 3-3.5 MPa and a constant temperature reaction.
[0037] In the carbon dioxide hydrogenation reaction, in order to improve the conversion rate of carbon dioxide and the yield of the target product (methanol), the catalyst is a crucial link. Among them, copper-based catalysts have high low-pressure activity and low cost, which has good advantages. Based on this, in the technical solution of the present invention, the copper-based catalyst is prepared by solution plasma technology.
[0038] First, the polarity and other properties of the solvent will affect the efficiency and selectivity of the catalytic reaction. Different from the pure water solvent system, the solvent system of adding water to isopropanol is conducive to the rapid dissolution and dispersion of copper salts, and the weakly coordinated solvent is conducive to the rapid dissolution and dispersion of Cu salts. 0 , Cu + Dynamic migration promotes Cu 0 , Cu + Diffusion and oxidation during the hydrogenation catalysis process. 0 , Cu + The surrounding charge distribution is optimized, accelerating the adsorption and desorption process of the gas. 0 , Cu + It is beneficial to quickly dissociate and activate hydrogen, that is, it increases the concentration of H atoms, accelerates the hydrogenation reaction, and promotes the formation of methanol.
[0039] In order to improve the stability of the catalyst, the present invention adds citric acid to adjust the system to a strong acid environment. The present invention uses citric acid as a complexing agent. Citric acid is a tribasic acid with a tetradentate ligand, which forms a soluble metal chelate with the free metal ions in the salt solution. In the copper solution, the Cu 0 , Cu + The dispersion of the carboxyl group and Cu is precisely controlled to combine them, which ultimately enhances the stability of the catalyst in adsorbing H atoms and O atoms. Then, during the solution plasma treatment process, the NO2 is decomposed and oxidized to form nano-scale powders. However, this process should strictly control parameters such as voltage and frequency.
[0040] The present invention utilizes solution plasma technology to improve the dispersibility of catalyst particles, and accurately refines metal grains by adjusting the reaction conditions in a gentle and simple manner, produces oxygen defects, improves the chemical adsorption capacity of the catalyst, and increases the number of active sites of the catalyst as a whole, which is difficult to achieve with conventional metal loading methods. The process does not involve the high temperature calcination step of the metal precursor, effectively prevents the aggregation of metal particles, and greatly reduces the impact of the metal loading step on the catalyst carrier. At the same time, this method of preparing loaded metal particles using solution plasma can minimize the impact of the metal loading process on the carrier during catalyst preparation. This operation constructs an efficient catalyst by designing catalyst active sites, which can not only provide abundant active sites for catalytic reaction, but also optimizes the catalyst electronic interaction ability in the catalytic carbon dioxide hydrogenation reaction system, thereby affecting the efficient reaction of carbon dioxide hydrogenation on the catalyst surface.
[0041] Copper-based catalysts supported on metal oxides and metalloid oxides have better reaction activity. 0 , Cu + The interaction with oxygen vacancies at the interface promotes the formation of active species and promotes the Cu 0 , Cu + Uniformly loaded. The carrier and Cu 0 , Cu + The active interface is formed, and the reduced catalyst enhances the interaction between the two, accelerates the combination of oxygen atoms, promotes the synthesis of methanol from the *HCOO (* indicates adsorption state) intermediate, and is beneficial to improving its catalytic activity.
[0042] Furthermore, when used, quartz sand is added. As an inert material, quartz sand usually provides support, ensures the height of the "bed" in a high temperature and high pressure environment, and enhances the mechanical strength of the catalyst, effectively protects the catalyst, improves its thermal conductivity, prevents it from sintering and agglomerating, and is conducive to maintaining its stability. At the same time, the low purity of quartz sand will cause a decrease in catalytic activity. The calcium oxide on the surface of the quartz sand is washed by the hydrogenation material and adheres to the surface of the catalyst, which easily covers the active sites of the catalyst. Therefore, the quartz sand should be pretreated to remove impurities.
[0043] In the process of synthesizing methanol from carbon dioxide, hydrogen acts as a reducing agent and directly participates in the hydrogenation catalytic reaction. Increasing hydrogen to provide sufficient reducing equivalents is beneficial to increasing the methanol yield. Nitrogen has an important influence on product distribution and promotes the synthesis of methanol by changing the chemical environment around the catalyst.
[0044] According to a series of experiments conducted by technicians, when nano-scale metal particles prepared by solution plasma are used in the preparation of carbon dioxide hydrogenation catalysts, it is possible to prepare loaded metal particles and control the size of metal particles, thereby obtaining a catalyst with good dispersion and large effective metal specific surface area. As the hydrogenation reaction temperature increases, the carbon dioxide conversion rate increases, but the methanol selectivity decreases. The reason is that the hydrogenation methanol synthesis reaction (ΔH 298 k =-49.7 kJ / mol) is an exothermic reaction, while the reverse water-gas shift reaction (i.e., the reaction that produces CO, ΔH 298 k = +41.2 kJ / mol) is an endothermic reaction, and the reaction temperature is too high, resulting in a significant increase in CO selectivity. According to a series of reactions, hydrogenation at about 300°C can produce methanol in high yield. In addition, since the hydrogenation of carbon dioxide to methanol involves multiple elementary reactions, multiple intermediates will be produced. As the hydrogenation catalytic reaction proceeds, *HCOO and *OCH3 intermediates are formed, which are further hydrogenated to produce methanol.
[0045] The beneficial effects of the present invention are as follows:
[0046] (1) The carrier part of the copper-based catalyst of the present invention can be directly purchased, and the metal loading is achieved by a solution plasma method, which requires less chemical agents for preparation and the synthesis process is environmentally friendly;
[0047] (2) The present invention constructs a copper-based catalyst with excellent metal dispersion, high effective metal surface area, and uniform metal loading particles. The effective component loading rate is high, and after long-term use, it is found that the catalyst has strong stability;
[0048] (3) The copper-based catalyst provided by the present invention has more abundant and effective metal active sites, that is, it has high catalytic activity and can efficiently convert carbon dioxide. After hydrogenation catalysis, the methanol yield obtained is high. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 A schematic diagram of a solution plasma treatment device used in the present invention;
[0050] Figure 2 This is an electron microscope characterization of the catalyst supported by zinc zirconium oxide. DETAILED DESCRIPTION
[0051] The present invention is further described in detail below in conjunction with specific embodiments and the accompanying drawings. A person of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by a person of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0052] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.
[0053] Example 1
[0054] A method for preparing a copper-based catalyst using solution plasma and its application in carbon dioxide hydrogenation, the method comprising:
[0055] 1) Take 15 mL of isopropanol and 135 mL of water and mix them evenly to obtain a mixed solution, add 0.11925 g of copper nitrate trihydrate and mix evenly, add 0.1 mol / L citric acid aqueous solution to adjust the pH value of the solution to 3, transfer the solution to the equipment, turn on the high-voltage pulse current while stirring, keep discharging for 15 minutes, then pause the discharge for 5 minutes, continue the discharge for 15 minutes, and end the discharge after 45 minutes of cyclic discharge;
[0056] The equipment parameters are: voltage 5.5 kV, frequency 25 kHz, pulse width 2.5 μs;
[0057] After the treatment, a plasma solution is obtained;
[0058] 2) taking out the plasma solution, adding 0.6 g of zinc zirconium oxide, stirring at room temperature for 12 h, centrifuging and drying to obtain a copper-based catalyst powder;
[0059] 3) The copper-based catalyst powder is pressed and sieved to obtain catalyst particles with a particle size of 40 mesh, quartz sand is pickled with 16 wt % hydrochloric acid, 5 g of quartz sand is added per gram of catalyst particles and mixed evenly, the mixture is transferred to a carbon dioxide hydrogenation reactor, and the lower end of the catalyst is supported by quartz wool;
[0060] 4) Controlling the carbon dioxide, hydrogen and nitrogen to be charged in a volume ratio of 1:3:1 by a mass flow meter to obtain a mixed gas, and introducing the mixed gas into a carbon dioxide hydrogenation reactor, the total gas flow rate is controlled at 50 mL / min, and the pressure is controlled at 300° C. by a back pressure valve to be 3 MPa, and the reaction is carried out at a constant temperature.
[0061] The copper-based catalyst prepared in this example was characterized, and its hydrogenation catalytic performance was tested. The testing method is as follows.
[0062] 1. Conversion rate
[0063] The CO2 conversion rate was calculated by the N2 internal standard method, and the calculation formula is as follows:
[0064]
[0065] Where GHSV represents the reaction gas space velocity, L·g -1 ·h -1 , represents the gas volume fraction;
[0066] 2. Product space-time yield
[0067] The methanol space-time yield was calculated by the C-based normalization method, and the calculation formula is as follows:
[0068]
[0069] Wherein, m is the mass of methanol recovered, g, and m1 represents the maximum mass of methanol that can be converted by CO2, g;
[0070] 3. Product selectivity
[0071] Methanol selectivity was calculated by C-based normalization method, and the calculation formula is as follows:
[0072]
[0073] Where m1 represents the methanol space-time yield, g MeOH kg -1 ·h -1 , t represents the reaction time, h, m2 represents the mass of the catalyst, kg, and m represents the mass of carbon dioxide consumed in the reaction, g;
[0074] 4. Stability
[0075] The copper-based catalyst in this example is used for 10 cycles of catalysis under the same conditions. If the carbon dioxide conversion rate decreases by less than 3% after the last hydrogenation catalysis, it is a catalyst with good cycle stability.
[0076] In addition, a low-temperature catalytic activity test was conducted at 5°C. If the carbon dioxide conversion rate decreased by less than 3% after hydrogenation catalysis, the catalyst had good cycle stability.
[0077] If the above two conditions are met, the catalyst is recorded as "qualified", otherwise it is recorded as "unqualified".
[0078] The results are as follows.
[0079] <![CDATA[CO2 conversion rate (%)]]> <![CDATA[Methanol space-time yield (g MeOH ·kg -1 ·h -1 )]]> Methanol selectivity (%) stability 22.3 222.8 29.6 qualified
[0080] like Figure 2 The characterization diagram shows that Cu is successfully loaded on the zinc zirconium oxide carrier. The present invention uses a new metal precursor treatment method, using solution plasma to treat the metal precursor salt solution. It is characterized that the catalyst particle size is uniform and the size is 2.5-3.5nm. While increasing the metal dispersion, the effective area of the active metal of the catalyst is greatly increased. It can effectively regulate the size of the loaded metal nanoparticles and improve the efficiency of carbon dioxide hydrogenation to methanol. According to the results in the table, due to the high relative proportion of oxygen defects in the catalyst prepared by the present invention, the carbon dioxide conversion rate is high and the methanol selectivity is high, so a high yield of methanol is obtained. Due to Cu 2+ Reduction to Cu + , Cu + Reduction to Cu 0 , and CuO x The (x=1, 2) content is low and the active species are exposed, thus making the catalyst have excellent low-temperature activity.
[0081] Example 2
[0082] A method for preparing a copper-based catalyst using solution plasma and its application in carbon dioxide hydrogenation, the method comprising:
[0083] 1) Take 15 mL of isopropanol and 135 mL of water and mix them evenly to obtain a mixed solution, add 0.12998 g of copper nitrate trihydrate and mix evenly, add 0.1 mol / L citric acid aqueous solution to adjust the pH value of the solution to 3, transfer the solution to the equipment, turn on the high-voltage pulse current while stirring, keep discharging for 15 minutes, then pause the discharge for 5 minutes, continue the discharge for 15 minutes, and end the discharge after 45 minutes of cyclic discharge;
[0084] The equipment parameters are: voltage 5.5 kV, frequency 25 kHz, pulse width 2.5 μs;
[0085] After the treatment, a plasma solution is obtained;
[0086] 2) taking out the plasma solution, adding 0.6 g of zinc zirconium oxide, stirring at room temperature for 12 h, centrifuging and drying to obtain a copper-based catalyst powder;
[0087] 3) The copper-based catalyst powder is pressed and sieved to obtain catalyst particles with a particle size of 40 mesh, quartz sand is pickled with 16 wt % hydrochloric acid, 5 g of quartz sand is added per gram of catalyst particles and mixed evenly, the mixture is transferred to a carbon dioxide hydrogenation reactor, and the lower end of the catalyst is supported by quartz wool;
[0088] 4) Controlling the carbon dioxide, hydrogen and nitrogen to be charged in a volume ratio of 1:3:1 by a mass flow meter to obtain a mixed gas, and introducing the mixed gas into a carbon dioxide hydrogenation reactor, the total gas flow rate is controlled at 50 mL / min, and the pressure is controlled at 300° C. by a back pressure valve to be 3 MPa, and the reaction is carried out at a constant temperature.
[0089] The copper-based catalyst prepared in this example was characterized, and its hydrogenation catalytic performance was tested in the same manner as in Example 1. The results are as follows.
[0090] <![CDATA[CO2 conversion rate (%)]]> <![CDATA[Methanol space-time yield (g MeOH ·kg -1 ·h -1 )]]> Methanol selectivity (%) stability 24.8 238.2 29.8 qualified
[0091] After the copper salt is compounded with the carrier, the loading amount of Cu has a significant effect on the catalytic effect. According to the results in the tables of Example 1 and Example 2, a higher loading amount obtains a catalyst with abundant active sites and high porosity, which is conducive to the hydrogenation catalytic reaction. Moreover, the copper-based catalyst with high porosity can maintain the stability of the catalyst itself in a low temperature environment, avoid the loss of active species due to cracking and fragmentation, and ensure the hydrogenation catalytic activity. Thus, the carbon dioxide conversion rate is improved and the methanol yield is improved.
[0092] Example 3
[0093] A method for preparing a copper-based catalyst using solution plasma and its application in carbon dioxide hydrogenation, the method comprising:
[0094] 1) Take 15 mL of isopropanol and 135 mL of water and mix them evenly to obtain a mixed solution, add 0.14070 g of copper nitrate trihydrate and mix evenly, add 0.1 mol / L citric acid aqueous solution to adjust the pH value of the solution to 3, transfer the solution to the equipment, turn on the high-voltage pulse current while stirring, keep discharging for 15 minutes, then pause the discharge for 5 minutes, continue discharging for 15 minutes, and end the discharge after 45 minutes of cyclic discharge;
[0095] The equipment parameters are: voltage 5.5 kV, frequency 25 kHz, pulse width 2.5 μs;
[0096] After the treatment, a plasma solution is obtained;
[0097] 2) taking out the plasma solution, adding 0.6 g of zinc zirconium oxide, stirring at room temperature for 12 h, centrifuging and drying to obtain a copper-based catalyst powder;
[0098] 3) The copper-based catalyst powder is pressed and sieved to obtain catalyst particles with a particle size of 40 mesh, quartz sand is pickled with 16 wt % hydrochloric acid, 5 g of quartz sand is added per gram of catalyst particles and mixed evenly, the mixture is transferred to a carbon dioxide hydrogenation reactor, and the lower end of the catalyst is supported by quartz wool;
[0099] 4) Controlling the carbon dioxide, hydrogen and nitrogen to be charged in a volume ratio of 1:3:1 by a mass flow meter to obtain a mixed gas, and introducing the mixed gas into a carbon dioxide hydrogenation reactor, the total gas flow rate is controlled at 50 mL / min, and the pressure is controlled at 300° C. by a back pressure valve to be 3 MPa, and the reaction is carried out at a constant temperature.
[0100] The copper-based catalyst prepared in this example was characterized, and its hydrogenation catalytic performance was tested in the same manner as in Example 1. The results are as follows.
[0101] <![CDATA[CO2 conversion rate (%)]]> <![CDATA[Methanol space-time yield (g MeOH ·kg -1 ·h -1 )]]> Methanol selectivity (%) stability 23.5 224.0 29.6 qualified
[0102] In theory, the increase of copper loading is more conducive to hydrogenation catalysis, but in reality, 0 , Cu + The active site content decreases, and the Cu position distribution changes with the loading. In the case of high loading, a large amount of agglomerated copper oxide is formed, which is not conducive to the conversion of carbon dioxide. In addition, since the porosity of the catalyst in this example decreases, the pore volume decreases, and the active site structure changes caused by the expansion or contraction of the catalyst volume are more obvious, resulting in loss of active substances, thereby causing a decrease in methanol yield.
[0103] In combination with Examples 1 to 3, due to the good dispersion of metal crystals on the catalyst surface and the uniform metal particle size, a larger effective active metal surface area is achieved, which is conducive to efficient catalytic reaction and improves the carbon dioxide conversion rate and methanol yield in the catalytic conversion of carbon dioxide hydrogenation.
[0104] Example 4
[0105] A method for preparing a copper-based catalyst using solution plasma and its application in carbon dioxide hydrogenation, the method comprising:
[0106] 1) Take 15 mL of isopropanol and 135 mL of water and mix them evenly to obtain a mixed solution, add 0.12998 g of copper nitrate trihydrate and mix evenly, add 0.1 mol / L citric acid aqueous solution to adjust the pH value of the solution to 3, transfer the solution to the equipment, turn on the high-voltage pulse current while stirring, keep discharging for 15 minutes, then pause the discharge for 5 minutes, continue the discharge for 15 minutes, and end the discharge after 45 minutes of cyclic discharge;
[0107] The equipment parameters are: voltage 5.5 kV, frequency 25 kHz, pulse width 2.5 μs;
[0108] After the treatment, a plasma solution is obtained;
[0109] 2) taking out the plasma solution, adding 0.6 g of cerium oxide, stirring at room temperature for 12 hours, centrifuging and drying to obtain a copper-based catalyst powder;
[0110] 3) The copper-based catalyst powder is pressed and sieved to obtain catalyst particles with a particle size of 40 mesh, quartz sand is pickled with 16 wt % hydrochloric acid, 5 g of quartz sand is added per gram of catalyst particles and mixed evenly, the mixture is transferred to a carbon dioxide hydrogenation reactor, and the lower end of the catalyst is supported by quartz wool;
[0111] 4) Controlling the carbon dioxide, hydrogen and nitrogen to be charged in a volume ratio of 1:3:1 by a mass flow meter to obtain a mixed gas, and introducing the mixed gas into a carbon dioxide hydrogenation reactor, the total gas flow rate is controlled at 50 mL / min, and the pressure is controlled at 300° C. by a back pressure valve to be 3 MPa, and the reaction is carried out at a constant temperature.
[0112] The copper-based catalyst prepared in this example was characterized, and its hydrogenation catalytic performance was tested in the same manner as in Example 1. The results are as follows.
[0113] <![CDATA[CO2 conversion rate (%)]]> <![CDATA[Methanol space-time yield (g MeOH ·kg -1 ·h -1 )]]> Methanol selectivity (%) stability 23.3 229.9 29.7 qualified
[0114] According to the results in the table, the catalyst prepared using cerium oxide as the carrier also has high catalytic activity and excellent stability. + -O-Ce 3+ In the structure, Cu + The site adsorbs O atoms, while O-Ce 3+ The site dissociation activation effect is strong, which is beneficial to the conversion of carbon dioxide. However, in this example, the Cu ion site occupies less cationic sites of the "skeleton", and more Cu is dispersed on the catalyst surface. Therefore, the carbon dioxide conversion rate in this example is slightly lower than that in Example 2. It can be seen that the copper-based catalyst prepared with cerium oxide as a carrier also has a good development prospect.
[0115] Comparative Example 1
[0116] A method for preparing a copper-based catalyst using solution plasma and its application in carbon dioxide hydrogenation, the method comprising:
[0117] 1) Take 30 mL of isopropanol and 135 mL of water and mix them evenly to obtain a mixed solution, add 0.12998 g of copper nitrate trihydrate and mix evenly, add 0.1 mol / L citric acid aqueous solution to adjust the pH value of the solution to 3, transfer the solution to the equipment, turn on the high-voltage pulse current while stirring, keep discharging for 15 minutes, then pause the discharge for 5 minutes, continue the discharge for 15 minutes, and end the discharge after 45 minutes of cyclic discharge;
[0118] The equipment parameters are: voltage 5.5 kV, frequency 25 kHz, pulse width 2.5 μs;
[0119] After the treatment, a plasma solution is obtained;
[0120] 2) taking out the plasma solution, adding 0.6 g of zinc zirconium oxide, stirring at room temperature for 12 h, centrifuging and drying to obtain a copper-based catalyst powder;
[0121] 3) The copper-based catalyst powder is pressed and sieved to obtain catalyst particles with a particle size of 40 mesh, quartz sand is pickled with 16 wt % hydrochloric acid, 5 g of quartz sand is added per gram of catalyst particles and mixed evenly, the mixture is transferred to a carbon dioxide hydrogenation reactor, and the lower end of the catalyst is supported by quartz wool;
[0122] 4) Controlling the carbon dioxide, hydrogen and nitrogen to be charged in a volume ratio of 1:3:1 by a mass flow meter to obtain a mixed gas, and introducing the mixed gas into a carbon dioxide hydrogenation reactor, the total gas flow rate is controlled at 50 mL / min, and the pressure is controlled at 300° C. by a back pressure valve to be 3 MPa, and the reaction is carried out at a constant temperature.
[0123] The copper-based catalyst prepared in this example was characterized, and its hydrogenation catalytic performance was tested in the same manner as in Example 1. The results are as follows.
[0124] <![CDATA[CO2 conversion rate (%)]]> <![CDATA[Methanol space-time yield (g MeOH ·kg -1 ·h -1 )]]> Methanol selectivity (%) stability 22.9 211.4 27.3 qualified
[0125] The low isopropanol-water volume ratio of the present invention is conducive to reducing the side reaction of Fischer-Tropsch synthesis, that is, CO dissociates on the catalyst surface and is reduced to obtain a methylene intermediate to form a product. Otherwise, as shown in the results in the table of this example, other olefin by-products are generated, resulting in poor methanol selectivity and abnormally reduced methanol yield.
[0126] Comparative Example 2
[0127] A method for preparing a copper-based catalyst using solution plasma and its application in carbon dioxide hydrogenation, the method comprising:
[0128] 1) Take 15 mL of isopropanol and 135 mL of water and mix them evenly to obtain a mixed solution, add 0.14998 g of copper nitrate trihydrate and mix evenly, add 0.1 mol / L citric acid aqueous solution to adjust the pH value of the solution to 3, transfer the solution to the equipment, turn on the high-voltage pulse current while stirring, keep discharging for 15 minutes, then pause the discharge for 5 minutes, continue discharging for 15 minutes, and end the discharge after 45 minutes of cyclic discharge;
[0129] The equipment parameters are: voltage 5.5 kV, frequency 25 kHz, pulse width 2.5 μs;
[0130] After the treatment, a plasma solution is obtained;
[0131] 2) taking out the plasma solution, adding 0.6 g of zinc zirconium oxide, stirring at room temperature for 12 h, centrifuging and drying to obtain a copper-based catalyst powder;
[0132] 3) The copper-based catalyst powder is pressed and sieved to obtain catalyst particles with a particle size of 40 mesh, quartz sand is pickled with 16 wt % hydrochloric acid, 5 g of quartz sand is added per gram of catalyst particles and mixed evenly, the mixture is transferred to a carbon dioxide hydrogenation reactor, and the lower end of the catalyst is supported by quartz wool;
[0133] 4) Controlling the carbon dioxide, hydrogen and nitrogen to be charged in a volume ratio of 1:3:1 by a mass flow meter to obtain a mixed gas, and introducing the mixed gas into a carbon dioxide hydrogenation reactor, the total gas flow rate is controlled at 50 mL / min, and the pressure is controlled at 300° C. by a back pressure valve to be 3 MPa, and the reaction is carried out at a constant temperature.
[0134] The copper-based catalyst prepared in this example was characterized, and its hydrogenation catalytic performance was tested in the same manner as in Example 1. The results are as follows.
[0135] <![CDATA[CO2 conversion rate (%)]]> <![CDATA[Methanol space-time yield (g MeOH ·kg -1 ·h -1 )]]> Methanol selectivity (%) stability 18.8 189.3 28.4 Failure
[0136] In this example, the amount of copper salt used is further increased. After characterization, the loading amount of active species of the catalyst is further increased. However, the hydrogenation methanol synthesis reaction (ΔH 298 k =-49.7 kJ / mol) is an exothermic reaction, while the reverse water-gas shift reaction (i.e., the reaction that produces CO, ΔH 298 k = +41.2 kJ / mol) is an endothermic reaction, and theoretically, in the hydrogenation reaction, the reaction between the O atom on the catalyst and the H atom dissociated from the hydrogen to form OH is reversible. Continue the hydrogenation reaction until Cu 0 , Cu +The active sites adsorb H atoms until they are saturated. At this time, *OH (* indicates adsorption state) is difficult to decompose and is easy to further hydrogenate to form H2O. Although H2O is beneficial to reduce the formation of by-products, it promotes * OCH3 hydrolysis improves methanol selectivity. However, it is easy to accelerate Cu 0 , Cu + Oxidation and agglomeration occur, causing the copper-based catalyst to lose its catalytic activity, which has a devastating impact on the application of the catalyst and leads to low methanol yield.
[0137] Comparative Example 3
[0138] A method for preparing a copper-based catalyst using solution plasma and its application in carbon dioxide hydrogenation, the method comprising:
[0139] 1) Take 135 mL of water and mix well to obtain a mixed solution, add 0.12998 g of copper nitrate trihydrate and mix well, add 0.1 mol / L citric acid aqueous solution to adjust the pH value of the solution to 3, transfer the solution to the equipment, turn on the high-voltage pulse current while stirring, keep discharging for 15 minutes, then pause the discharge for 5 minutes, continue discharging for 15 minutes, and end the discharge after 45 minutes of cyclic discharge;
[0140] The equipment parameters are: voltage 5.5 kV, frequency 25 kHz, pulse width 2.5 μs;
[0141] After the treatment, a plasma solution is obtained;
[0142] 2) taking out the plasma solution, adding 0.6 g of zinc zirconium oxide, stirring at room temperature for 12 h, centrifuging and drying to obtain a copper-based catalyst powder;
[0143] 3) The copper-based catalyst powder is pressed and sieved to obtain catalyst particles with a particle size of 40 mesh, quartz sand is pickled with 16 wt % hydrochloric acid, 5 g of quartz sand is added per gram of catalyst particles and mixed evenly, the mixture is transferred to a carbon dioxide hydrogenation reactor, and the lower end of the catalyst is supported by quartz wool;
[0144] 4) Controlling the carbon dioxide, hydrogen and nitrogen to be charged in a volume ratio of 1:3:1 by a mass flow meter to obtain a mixed gas, and introducing the mixed gas into a carbon dioxide hydrogenation reactor, the total gas flow rate is controlled at 50 mL / min, and the pressure is controlled at 300° C. by a back pressure valve to be 3 MPa, and the reaction is carried out at a constant temperature.
[0145] The copper-based catalyst prepared in this example was characterized, and its hydrogenation catalytic performance was tested in the same manner as in Example 1. The results are as follows.
[0146] <![CDATA[CO2 conversion rate (%)]]> <![CDATA[Methanol space-time yield (g MeOH ·kg -1 ·h -1 )]]> Methanol selectivity (%) stability 19.1 165.9 25.2 qualified
[0147] In this case, the hydroxyl group is not connected, which is not conducive to maintaining a high proportion of defective oxygen, resulting in the intermediate species *HCOO, * The conversion of OCH3 to methanol is inhibited. 0 , Cu + The diffusion of CO2 is inhibited, and the adsorption and activation effects on CO2 are reduced, resulting in the decomposition of the intermediates in the hydrogenation catalytic reaction to form CO. The dissociation leads to a decrease in the methanol yield, which in turn increases the CO selectivity.
[0148] Comparative Example 4
[0149] A method for preparing a copper-based catalyst using solution plasma and its application in carbon dioxide hydrogenation, the method comprising:
[0150] 1) Take 15 mL of isopropanol and 135 mL of water and mix them evenly to obtain a mixed solution, add 0.12998 g of copper nitrate trihydrate and mix evenly, add 0.1 mol / L citric acid aqueous solution to adjust the pH value of the solution to 2.5, transfer the solution to the equipment, turn on the high-voltage pulse current while stirring, keep discharging for 15 minutes, then pause the discharge for 5 minutes, continue discharging for 15 minutes, and end the discharge after 45 minutes of cyclic discharge;
[0151] The equipment parameters are: voltage 5.5 kV, frequency 25 kHz, pulse width 2.5 μs;
[0152] After the treatment, a plasma solution is obtained;
[0153] 2) taking out the plasma solution, adding 0.6 g of zinc zirconium oxide, stirring at room temperature for 12 h, centrifuging and drying to obtain a copper-based catalyst powder;
[0154] 3) The copper-based catalyst powder is pressed and sieved to obtain catalyst particles with a particle size of 40 mesh, quartz sand is pickled with 16 wt % hydrochloric acid, 5 g of quartz sand is added per gram of catalyst particles and mixed evenly, the mixture is transferred to a carbon dioxide hydrogenation reactor, and the lower end of the catalyst is supported by quartz wool;
[0155] 4) Controlling the carbon dioxide, hydrogen and nitrogen to be charged in a volume ratio of 1:3:1 by a mass flow meter to obtain a mixed gas, and introducing the mixed gas into a carbon dioxide hydrogenation reactor, the total gas flow rate is controlled at 50 mL / min, and the pressure is controlled at 300° C. by a back pressure valve to be 3 MPa, and the reaction is carried out at a constant temperature.
[0156] The copper-based catalyst prepared in this example was characterized, and its hydrogenation catalytic performance was tested in the same manner as in Example 1. The results are as follows.
[0157] <![CDATA[CO2 conversion rate (%)]]> <![CDATA[Methanol space-time yield (g MeOH ·kg -1 ·h -1 )]]> Methanol selectivity (%) stability 24.9 232.7 28.6 qualified
[0158] In this example, the dosage of citric acid is further increased to adjust the solution pH to 2.5. According to the results in the table, it can be seen that although a large amount of citric acid will increase the carbon dioxide conversion rate, it will lead to a decrease in methanol selectivity, which indicates that continuing to increase the dosage of citric acid is not conducive to catalytic production of methanol.
[0159] Comparative Example 5
[0160] A method for preparing a copper-based catalyst using solution plasma and its application in carbon dioxide hydrogenation, the method comprising:
[0161] 1) Take 15 mL of isopropanol and 135 mL of water and mix them evenly to obtain a mixed solution, add 0.12998 g of copper nitrate trihydrate and mix evenly, add 0.1 mol / L citric acid aqueous solution to adjust the pH value of the solution to 3, transfer the solution to the equipment, turn on the high-voltage pulse current while stirring, keep discharging for 15 minutes, then pause the discharge for 5 minutes, continue the discharge for 15 minutes, and end the discharge after 45 minutes of cyclic discharge;
[0162] The equipment parameters are: voltage 4.5 kV, frequency 20 kHz, pulse width 2.5 μs;
[0163] After the treatment, a plasma solution is obtained;
[0164] 2) taking out the plasma solution, adding 0.6 g of zinc zirconium oxide, stirring at room temperature for 12 h, centrifuging and drying to obtain a copper-based catalyst powder;
[0165] 3) The copper-based catalyst powder is pressed and sieved to obtain catalyst particles with a particle size of 40 mesh, quartz sand is pickled with 16 wt % hydrochloric acid, 5 g of quartz sand is added per gram of catalyst particles and mixed evenly, the mixture is transferred to a carbon dioxide hydrogenation reactor, and the lower end of the catalyst is supported by quartz wool;
[0166] 4) Controlling the carbon dioxide, hydrogen and nitrogen to be charged in a volume ratio of 1:3:1 by a mass flow meter to obtain a mixed gas, and introducing the mixed gas into a carbon dioxide hydrogenation reactor, the total gas flow rate is controlled at 50 mL / min, and the pressure is controlled at 300° C. by a back pressure valve to be 3 MPa, and the reaction is carried out at a constant temperature.
[0167] The copper-based catalyst prepared in this example was characterized, and its hydrogenation catalytic performance was tested in the same manner as in Example 1. The results are as follows.
[0168] <![CDATA[CO2 conversion rate (%)]]> <![CDATA[Methanol space-time yield (g MeOH ·kg -1 ·h -1 )]]> Methanol selectivity (%) stability 19.4 193.3 29.6 qualified
[0169] Based on Example 2, this example lowers the voltage and frequency parameters of the solution plasma device, which can cause incomplete decomposition of nitrate ions. Under high energy, it reacts violently with the reducing citric acid, causing the solution to splash and cause losses, resulting in the activation of Cu 0 , Cu + The reduction in content significantly affects the hydrogenation catalytic activity, resulting in low carbon dioxide conversion rate and low methanol yield.
[0170] Comparative Example 6
[0171] A method for preparing a copper-based catalyst using solution plasma and its application in carbon dioxide hydrogenation, the method comprising:
[0172] 1) Take 15 mL of isopropanol and 135 mL of water and mix them evenly to obtain a mixed solution, add 0.12998 g of copper nitrate trihydrate and mix evenly, add 0.1 mol / L citric acid aqueous solution to adjust the pH value of the solution to 3, transfer the solution to the equipment, turn on the high-voltage pulse current while stirring, keep discharging for 15 minutes, then pause the discharge for 5 minutes, continue the discharge for 15 minutes, and end the discharge after 45 minutes of cyclic discharge;
[0173] The equipment parameters are: voltage 6.5 kV, frequency 35 kHz, pulse width 2.5 μs;
[0174] After the treatment, a plasma solution is obtained;
[0175] 2) taking out the plasma solution, adding 0.6 g of zinc zirconium oxide, stirring at room temperature for 12 h, centrifuging and drying to obtain a copper-based catalyst powder;
[0176] 3) The copper-based catalyst powder is pressed and sieved to obtain catalyst particles with a particle size of 40 mesh, quartz sand is pickled with 16 wt % hydrochloric acid, 5 g of quartz sand is added per gram of catalyst particles and mixed evenly, the mixture is transferred to a carbon dioxide hydrogenation reactor, and the lower end of the catalyst is supported by quartz wool;
[0177] 4) Controlling the carbon dioxide, hydrogen and nitrogen to be charged in a volume ratio of 1:3:1 by a mass flow meter to obtain a mixed gas, and introducing the mixed gas into a carbon dioxide hydrogenation reactor, the total gas flow rate is controlled at 50 mL / min, and the pressure is controlled at 300° C. by a back pressure valve to be 3 MPa, and the reaction is carried out at a constant temperature.
[0178] The copper-based catalyst prepared in this example was characterized, and its hydrogenation catalytic performance was tested in the same manner as in Example 1. The results are as follows.
[0179] <![CDATA[CO2 conversion rate (%)]]> <![CDATA[Methanol space-time yield (g MeOH ·kg -1 ·h -1 )]]> Methanol selectivity (%) stability 18.2 186.3 29.4 qualified
[0180] Based on Example 2, the voltage and frequency parameters of the solution plasma equipment were increased in this example. At this time, the nitrate, citric acid complex and free citric acid were completely decomposed and no longer reacted, but the particles aggregated, resulting in the activation of Cu 0 , Cu + The interaction with the support becomes worse, thus affecting the hydrogenation catalytic performance, resulting in low carbon dioxide conversion and low methanol yield.
[0181] Combining the results in the tables of Comparative Examples 5 and 6, it can be found that the catalyst performance is greatly affected by the solution plasma process. Therefore, the present invention controls the parameters of the process equipment.
[0182] Comparative Example 7
[0183] A method for preparing a copper-based catalyst using solution plasma and its application in carbon dioxide hydrogenation, the method comprising:
[0184] 1) Take 15 mL of isopropanol and 135 mL of water and mix them evenly to obtain a mixed solution, add 0.12998 g of copper nitrate trihydrate and mix evenly, add 0.1 mol / L citric acid aqueous solution to adjust the pH value of the solution to 3, transfer the solution to the equipment, turn on the high-voltage pulse current while stirring, keep discharging for 15 minutes, then pause the discharge for 5 minutes, continue the discharge for 15 minutes, and end the discharge after 45 minutes of cyclic discharge;
[0185] The equipment parameters are: voltage 5.5 kV, frequency 25 kHz, pulse width 2.5 μs;
[0186] After the treatment, a plasma solution is obtained;
[0187] 2) taking out the plasma solution, adding 0.6 g of activated carbon, stirring at room temperature for 12 h, centrifuging and drying to obtain a copper-based catalyst powder;
[0188] 3) The copper-based catalyst powder is pressed and sieved to obtain catalyst particles with a particle size of 40 mesh, quartz sand is pickled with 16 wt % hydrochloric acid, 5 g of quartz sand is added per gram of catalyst particles and mixed evenly, the mixture is transferred to a carbon dioxide hydrogenation reactor, and the lower end of the catalyst is supported by quartz wool;
[0189] 4) Controlling the carbon dioxide, hydrogen and nitrogen to be charged in a volume ratio of 1:3:1 by a mass flow meter to obtain a mixed gas, and introducing the mixed gas into a carbon dioxide hydrogenation reactor, the total gas flow rate is controlled at 50 mL / min, and the pressure is controlled at 300° C. by a back pressure valve to be 3 MPa, and the reaction is carried out at a constant temperature.
[0190] The copper-based catalyst prepared in this example was characterized, and its hydrogenation catalytic performance was tested in the same manner as in Example 1. The results are as follows.
[0191] <![CDATA[CO2 conversion rate (%)]]> <![CDATA[Methanol space-time yield (g MeOH ·kg -1 ·h -1 )]]> Methanol selectivity (%) stability 20.0 199.6 28.4 Failure
[0192] In this case, activated carbon is used as the carrier. 0 , Cu + The active species content is low, so compared with copper-based catalysts prepared with metal oxides and metalloid oxides as carriers, the catalytic activity of this catalyst is poor. In addition, the combination of activated carbon and Cu is not good, resulting in poor catalyst stability. The catalyst is only through Cu 0 , Cu + The structure of activated carbon has no advantage in the hydrogenation catalysis of active species, that is, it has almost no promoting effect on combining oxygen atoms and promoting the synthesis of *HCOO intermediates. Therefore, the carbon dioxide conversion rate in this case is low.
[0193] Comparative Example 8
[0194] A method for preparing a copper-based catalyst by impregnation method and application thereof in carbon dioxide hydrogenation, the method comprising:
[0195] 1) 80 mL of water and 0.11925 g of copper nitrate trihydrate were mixed to obtain solution A, and 0.6 g of zinc zirconium oxide and 70 mL of water were mixed to obtain solution B;
[0196] 2) While stirring, slowly drop solution A into solution B, stir at room temperature for 4 h, heat in a water bath at 80° C., evaporate water, and dry to obtain a solid powder;
[0197] 3) calcining the solid powder at 500° C. for 5 h in an air atmosphere to obtain a copper-based catalyst;
[0198] 4) taking the copper-based catalyst powder, pressing and sieving to obtain catalyst particles with a particle size of 40 mesh, adding 5 g of quartz sand per gram of catalyst particles and mixing evenly, transferring the mixture to a carbon dioxide hydrogenation reactor, and supporting the lower end of the catalyst with quartz wool;
[0199] 5) Controlling the carbon dioxide, hydrogen and nitrogen to be charged in a volume ratio of 1:3:1 by a mass flow meter to obtain a mixed gas, and introducing the mixed gas into a carbon dioxide hydrogenation reactor, the total gas flow rate is controlled at 50 mL / min, and the pressure is controlled at 3 MPa by a back pressure valve at 400° C., and the reaction is carried out at a constant temperature.
[0200] The copper-based catalyst prepared in this example was characterized, and its hydrogenation catalytic performance was tested in the same manner as in Example 1. The results are as follows.
[0201] <![CDATA[CO2 conversion rate (%)]]> <![CDATA[Methanol space-time yield (g MeOH ·kg -1 ·h -1 )]]> Methanol selectivity (%) stability 25.2 193.0 20.4 qualified
[0202] In this case, the temperature of the hydrogenation reaction was further increased, and the carbon dioxide conversion rate increased, but the selectivity of methanol decreased. The reason is that the hydrogenation methanol reaction (ΔH 298 k =-49.7 kJ / mol) is an exothermic reaction, while the reverse water-gas shift reaction (i.e., the reaction that produces CO, ΔH 298 k =+41.2 kJ / mol) is an endothermic reaction, and the reaction temperature is too high, resulting in a significant increase in CO selectivity.
[0203] Comparative Example 9
[0204] A method for preparing a catalyst and application thereof in carbon dioxide hydrogenation, the method comprising:
[0205] 1) taking commercially available zinc zirconium oxide and sieving it to obtain catalyst particles with a particle size of 40 mesh;
[0206] 2) taking the copper-based catalyst powder, pressing and sieving to obtain catalyst particles with a particle size of 40 mesh, adding 5 g of quartz sand per gram of catalyst particles and mixing evenly, transferring the mixture to a carbon dioxide hydrogenation reactor, and supporting the lower end of the catalyst with quartz wool;
[0207] 3) Controlling the carbon dioxide, hydrogen and nitrogen to be charged in a volume ratio of 1:3:1 by a mass flow meter to obtain a mixed gas, and introducing the mixed gas into a carbon dioxide hydrogenation reactor, with the total gas flow rate controlled at 50 mL / min, and the pressure controlled at 300° C. by a back pressure valve to be 3 MPa, and reacting at a constant temperature.
[0208] The catalyst prepared in this example was characterized, and its hydrogenation catalytic performance was tested in the same manner as in Example 1. The results are as follows.
[0209]
[0210]
[0211] Compared with Example 2, in this example, only zinc zirconium oxide is used as the main component of the catalyst. According to the results in the table, it can be analyzed that the catalyst in this example has a poor activation effect on carbon dioxide, a low intermediate content, and a significantly reduced methanol content obtained by conversion with hydrogen. 0 , Cu + It has an inductive effect, that is, it induces more Cu 0 , Cu + Participate in hydrogenation reaction, atomically dispersed Cu 0 , Cu +It is easy to form interfacial active sites on the surface of oxygen-deficient metal oxides and metalloid oxides, so the catalyst has excellent catalytic activity. This shows the importance of metal oxide and metalloid oxide carriers to the Cu loading effect and catalytic performance of the catalyst.
Claims
1. A method for preparing a copper-based catalyst using solution plasma, characterized in that: The method comprises: 1) mixing acyclic alcohol and a dispersant to obtain a mixed solution, adding copper salt to mix evenly, adjusting the pH value of the solution, and transferring the solution to a device for solution plasma treatment to obtain a plasma solution; 2) The mixed solution is taken out, and carrier powder is added to perform mechanical mixing, and the mixture is centrifuged and dried to obtain copper-based catalyst powder.
2. The method for preparing a copper-based catalyst using solution plasma according to claim 1, characterized in that: Step 1) the acyclic alcohol is isopropanol; Step 1) the dispersant is water, and the acyclic alcohol and the dispersant are prepared in a volume ratio of 1: (9-10); Step 1) The copper salt is copper nitrate trihydrate, and its dosage is 0.795-0.938 g / L mixed solution.
3. The method for preparing a copper-based catalyst using solution plasma according to claim 1, characterized in that: Step 1) The process of adjusting the pH value of the solution is: adding citric acid aqueous solution to adjust the pH value of the solution to 2.9-3; The concentration of the citric acid aqueous solution is 0.1-0.2 mol / L.
4. A method for preparing a copper-based catalyst using solution plasma according to claim 1, 2 or 3, characterized in that: Step 1) The solution plasma treatment is to start the high-voltage pulse current while stirring, keep discharging for 15 minutes, then pause the discharge for 5 minutes, continue the discharge for 15 minutes, and end the discharge after the cycle discharge for 45 minutes. The equipment parameters are as follows: The voltage is 5-6 kV, the frequency is 20-30 kHz, and the pulse width is 2-3 μs.
5. The method for preparing a copper-based catalyst using solution plasma according to claim 1, characterized in that: Step 2) The carrier powder is zeolite molecular sieve and / or hydrotalcite and / or alumina and / or cerium oxide and / or zinc zirconium oxide, and the amount thereof is 5-6.5 g / g copper salt.
6. A method for preparing a copper-based catalyst using solution plasma according to claim 1 or 5, characterized in that: Step 2) The mechanical mixing is carried out at room temperature and stirred for 12 to 15 hours.
7. Use of a copper-based catalyst prepared by the method according to any one of claims 1 to 6, characterized in that: The copper-based catalyst is used for titanium dioxide hydrogenation reaction.
8. The use according to claim 7, characterized in that: When the application is: The copper-based catalyst powder is tableted and sieved to obtain catalyst particles, silicate minerals are added and mixed evenly, the mixture is transferred to a carbon dioxide hydrogenation reactor, and the mixed gas is introduced into the carbon dioxide hydrogenation reactor to carry out a hydrogenation reaction.
9. The use according to claim 8, characterized in that: The tabletting and screening is to pass the formed catalyst particles through a 40-60 mesh sieve; The silicate mineral is quartz sand, and its usage is 5-5.2 g / g catalyst particles; The quartz sand is pickled with hydrochloric acid at a concentration of 16-18 wt%.
10. The use according to claim 1, characterized in that: Step 4) the mixed gas includes carbon dioxide, hydrogen and nitrogen, and the carbon dioxide, hydrogen and nitrogen are inflated according to a volume ratio of 1: (2.5-3.5): (0.5-1.5) by a mass flow meter, and the total gas flow rate is controlled at 50-55 mL / min; Step 4) The hydrogenation reaction is carried out at 300-350°C with a controlled pressure of 3-3.5 MPa and a constant temperature reaction.
